2014
DOI: 10.1038/eye.2014.129
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pain during intravitreal Ozurdex injections vs intravitreal bevacizumab injections

Abstract: Purpose The purpose was to evaluate the pain associated with intravitreal Ozurdex injections, and to compare it with that associated with intravitreal bevacizumab injections. Methods The study included 57 eyes of 57 patients who received an intravitreal Ozurdex injection at our institution. Pain was measured by the visual analog scale (VAS). Additional parameters recorded included age, sex, indication for the injection, number of previous Ozurdex injections in the study eye, presence of diabetes mellitus, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Knecht et al 17 reported that tunnelled injections were not associated with increased pain compared to straight injections. Moisseiev et al 18 found no significant difference between intravitreal injections of dexamethasone implant and bevacizumab in terms of pain. In our study, we also found no significant difference between intravitreal injections of dexamethasone implant, ranibizumab, and aflibercept in terms of pain.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Knecht et al 17 reported that tunnelled injections were not associated with increased pain compared to straight injections. Moisseiev et al 18 found no significant difference between intravitreal injections of dexamethasone implant and bevacizumab in terms of pain. In our study, we also found no significant difference between intravitreal injections of dexamethasone implant, ranibizumab, and aflibercept in terms of pain.…”
Section: Discussionmentioning
confidence: 97%
“…Moisseiev et al 18 reported there was no difference between eyes injected for the first time and eyes that were previously injected and lens status in terms of intensity of pain. Our study also showed that firsttime injections were not associated with more pain than eyes that underwent previous injections.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the relatively large diameter of the injector needle, the level of pain associated with the insertion procedure is not appreciably different from that produced by intravitreal anti-VEGF treatment, as administered with a 28- to 30-gauge needle. 55 Since the implant is biodegradable, subsequent implant(s) can be inserted without the need for surgical removal of the existing implant.…”
Section: Dexamethasone Intravitreal Drug Delivery Systemmentioning
confidence: 99%
“…Despite the larger gauge and use of a tunneled incision, dexamethasone implant injection was not found to be more painful than anti-VEGF injection [94].…”
Section: Dexamethasonementioning
confidence: 99%